"The Will to Adorn": Nick Cave's Soundsuits and the Queer Reframing of Black Masculinity. Issue 3 (4th May 2017) - Lamm, Kimberly
ABSTRACT: This article analyses Nick Cave's "soundsuits"—striking for their elaborately ornamented forms and vibrant colours—as queer reframings of black masculinity. Drawing on scholarship in African American studies that examines the production of black masculinity in response to racial violence, the article explores how Cave's soundsuits (produced from 1991 to 2011) can be understood in relationship to the beating of Rodney King that took place in Los Angeles in 1991. This exploration entails tracing how Cave's artwork alludes to the history of the black dandy, considered by many scholars to be an emblematic figure of the black sartorial imagination. By queering and elaborating on the adornment associated with the black dandy, Cave defies the racist and sexist subtexts of long-standing arguments against display and ornamentation to create a defence against the systemic violence inflicted upon the black male body in the US.